PENERAPAN PENGENDALIAN INTERN ATAS BIAYA BAHAN BAKU, BIAYA TENAGA KERJA LANGSUNG DAN BIAYA OVERHEAD DALAM PENINGKATAN EFISIENSI BIAYA PRODUKSI PADA PT. INTI INDOSAWIT SUBUR (Studi Kasus Pabrik Buatan Satu PT. Inti Indosawit Subur - Pangkalan Kerinci) - Melisa Elizabeth; Lamria Sagala (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
This study aims to analyze the application of internal control over the cost of raw materials, direct labor costs, and overhead costs in increasing the efficiency of production costs at PT. Subur Indosawit Core. The research method used is descriptive method, this type of research uses qualitative data and quantitative data. Sources of data used by researchers are secondary data and primary data. Data collection techniques are interviews and documentation. For the sustainability of the company, it is very necessary for a control to be able to utilize costs as well as possible in accordance with the expenses. Based on the discussion and research, the results were obtained, namely the application of internal control has been implemented effectively and efficiently. In addition, the resources owned by the company can have a positive impact in terms of production cost efficiency, but in 2021 factory overhead has not been effective and efficient because the realization is greater than the budget. Because there is a difference in variance in 2021 which is caused by several factors such as the use of spare parts, maintenance of machines, and the use of heavy equipment which causes the ineffective and efficient use of overhead costs that exceed the budget set in the factory costs. The realization of overhead costs in 2021 was IDR 12,535,921,608 and the overhead cost budget in 2021 was IDR 11,915,510,648 with a detrimental difference of IDR 620,410,960. This is due to the lack of supervision and checking of factory machines in producing a large number of materials that exceed the budget in 2021. The company has implemented controls for each factory cost but there is still a variance, so for the next year the company must evaluate more than the history of the previous year to be able to control factory costs effectively and efficiently.